Risk factors for hidden blood loss in unilateral biportal endoscopic lumbar spine surgery - Guo, Sijia; Tan, Haining; Meng, Hai; Li, Xiang; Su, Nan; Yu, Linjia; Lin, Jisheng; An, Ning; Yang, Yong; Fei, Qi (Frontiers in Surgery, 2022)
Background Unilateral biportal endoscopic (UBE) spine surgery is a minimally invasive procedure for treating lumbar disorders. Hidden blood loss (HBL) is easily ignored by surgeons because blood loss is less visible. However, there are limited studies on HBL in UBE spine surgery. This study aimed to evaluate HBL and its possible risk factors in patients undergoing UBE spine surgery. Methods Patients with lumbar disc herniation or lumbar spinal stenosis who underwent unilateral biportal endoscopic surgery between December 2020 and February 2022 at our hospital were retrospectively analyzed. Patient demographics, blood loss-related parameters, and surgical and radiological information were also collected. Pearson or Spearman correlation analysis was conducted to determine the association between clinical characteristics and HBL. Multivariate linear regression analysis was used to determine the independent risk factors for HBL. Results Fifty-two patients (17 males and 35 females) were retrospectively enrolled in this study. The mean total blood loss (TBL) volume was 434 ± 212 ml, and the mean HBL volume was 361 ± 217 ml, accounting for 77.9% of the TBL in patients who underwent UBE surgery. Multivariate linear regression analysis revealed that HBL was positively associated with operation time (P = 0.040) and paraspinal muscle thickness at the target level (P = 0.033). Conclusions The amount of HBL in patients undergoing UBE surgery should not be neglected. Operation time and paraspinal muscle thickness at the target level may be independent risk factors for HBL.